2016
DOI: 10.1097/mlr.0000000000000574
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Patients at Risk for 3-Day Postdischarge Readmissions, ED Visits, and Deaths

Abstract: The 3-day REDD model predicts high-risk patients with fair discriminative power. The discriminative power of the 30-day REDD model is also better than the previously reported models under similar settings. The 3-day REDD model has been implemented and is being used to identify patients at risk for AEs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Overall, 29.5% of the studies reviewed focused on SBDH factors associated with healthcare access and quality, 24.7% focused on economic stability, 20% focused on social and community context, 16.3% focused on neighborhood and built environment, and 9.5% focused on education access and quality. Widely studied SBDH factors include substance use/abuse (9%) [ 14 , 16 , 20 - 35 ], education (7.3%) [ 16 , 21 , 36 - 46 ], employment status (6.3%) [ 16 , 20 , 21 , 23 , 31 , 36 , 38 , 39 , 45 - 48 ], socioeconomic status (6.3%) [ 29 , 39 , 44 , 46 , 49 - 56 ], lifestyle (5.8%) [ 22 , 29 , 32 , 43 , 57 - 63 ], socioeconomic factors (5.3%) [ 28 , 38 , 39 , 46 , 58 , 63 - 67 ], diet (5.3%) [ 21 , 22 , 26 , 43 , 58 , 68 - 72 ], housing status (5.3%) [ 16 , 21 , 33 , 35 , 38 , 46 , 73 - 76 ], social support (5.3%) [ 14 , 15 , 35 , 74 , 77 - 82 ], physical activity (4.8%) [ 20 , 31 , 40 , 58 , ...…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Overall, 29.5% of the studies reviewed focused on SBDH factors associated with healthcare access and quality, 24.7% focused on economic stability, 20% focused on social and community context, 16.3% focused on neighborhood and built environment, and 9.5% focused on education access and quality. Widely studied SBDH factors include substance use/abuse (9%) [ 14 , 16 , 20 - 35 ], education (7.3%) [ 16 , 21 , 36 - 46 ], employment status (6.3%) [ 16 , 20 , 21 , 23 , 31 , 36 , 38 , 39 , 45 - 48 ], socioeconomic status (6.3%) [ 29 , 39 , 44 , 46 , 49 - 56 ], lifestyle (5.8%) [ 22 , 29 , 32 , 43 , 57 - 63 ], socioeconomic factors (5.3%) [ 28 , 38 , 39 , 46 , 58 , 63 - 67 ], diet (5.3%) [ 21 , 22 , 26 , 43 , 58 , 68 - 72 ], housing status (5.3%) [ 16 , 21 , 33 , 35 , 38 , 46 , 73 - 76 ], social support (5.3%) [ 14 , 15 , 35 , 74 , 77 - 82 ], physical activity (4.8%) [ 20 , 31 , 40 , 58 , ...…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies [ 24 , 28 , 49 , 54 , 58 , 60 , 64 , 70 , 84 , 92 , 93 , 95 ] used tree-based machine learning (ML) algorithms, including random forest and decision trees. Nau et al utilized nonparametric machine learning methods such as Conditional Random Forest (CRF) to identify the combination of community features that are most important for the prediction of obesogenic and obesoprotective environments for children [ 70 ], whereas Agrawal et al also used random forests along with gradient boosting methods and stacked generalization methods to attain their outcome using structured data [ 28 ]. Davoudi et al [ 24 ], Walsh et al [ 64 ], Grinspan et al [ 88 ], Feller et al [ 95 ], and Erickson et al [ 16 ] all made use of random forest variants.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Global Burden of Disease Study, published in 2020, analyzed global, regional and national sepsis incidence and mortality rates from 1990 to 2017 and reported that there were approximately 48.9 million cases of sepsis in 2017, with about 11 million sepsis-related deaths, accounting for 19.7% of all deaths worldwide [ 2 ]. High risk of rehospitalization and high cost of treatment for sepsis [ 3 , 4 ]. In the United States, sepsis was the most expensive condition treated, amounting to $38.2 billion or 8.8% of aggregate costs for all hospital stays in 2017 [ 5 ].…”
Section: Introductionmentioning
confidence: 99%